DNA typing the Asian elephant in Sri Lanka: An assessment of the genetic structure of the population & Establishment of paternity - Vandebona, H. (Faculty of Science, University of Colombo, 2001)
The Asian elephant. Elephas maximus is a globally threatened species. The elephant in Sri Lanka. Elephas maximus maximus, is a nominated subspecies of the Asian elephant. The elephant population in Sri Lanka is currently fragmented and restricted to a few isolated small jungle habitats. Maintenance of a high degree of genetic diversity within the population is essential for its future survival. There were two main objectives in this study. Firstly, as a prerequisite for future conservation and management measures, this study aimed at assessing the genetic population structure of the elephant in Sri Lanka with regard to geographic population structure and levels of genetic variability. The Second objective was, the development and use of DNA fingerprinting technology for the accurate assignment of paternity of elephants born in captivity. The establishment of paternity of progeny with certainty is also of considerable importance since the captive breeding programmes that are implemented for conservation of elephants depend critically on maintenance of genetic diversity within captive populations. Blood samples were collected for DNA extraction from one hundred and twenty seven Sri Lankan elephants (captive 120; wild 7), one elephant from Thailand and two African elephants. The genetic variability was analyzed in two mitochondrial genes i.e. cytochrome b (Cyt b) (n=70) and NADH dehydrogenase subunit 5 (ND5) (n=67) by Polymerase Chain Reaction (PCR) based amplification of elephant DNA using universal primers and analysis of DNA sequence data of their PCR products. The sequence divergence in the above two genes in the Asian elephant in three different geographical regions (Northern, Mahaweli and Southern) of Sri Lanka, was analyzed in this study. Analysis of sequence polymorphisms identified 12 polymorphic sites within the Cyt b sequence (410 bp) giving rise to 5 mtDNA haplotypes. ND5 sequence data (550 bp) revealed 9 polymorphic sites and 5 mtDNA haplotypes. A total of 67 elephant samples were analysed for sequence divergence in both genes, yielding seven distinct ND5-Cyt b mtDNA haplotypes.